Pola Komunikasi Keluarga Dan Beban Ganda Perempuan Nelayan Dalam Pengasuhan Anak - Zaimatur Rofiah Rofiah; Hilya Fathima Faza Firdausi (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2025)
This study aims to analyze the double burden experienced by fisherwomen and the role of family communication patterns in the context of childrearing in Warulor Village. Using a qualitative approach with a case study method, the findings reveal that fisherwomen bear a dominant double burden encompassing domestic responsibilities, economic contributions through fish marketing, as well as financial management and child care. Family communication patterns tend to be unequal and lack openness, particularly regarding financial issues, which encourages women to conceal economic difficulties, including indebtedness, as an adaptive strategy to maintain family stability. However, this communication strategy increases women’s psychological burden and has the potential to intensify marital conflict when financial problems are disclosed. Moreover, instructive and pressure-laden communication patterns affect mother–child relationships and influence children’s emotional and behavioral development. This study concludes that family communication plays a crucial role in maintaining patriarchal structures while simultaneously reinforcing the double burden borne by fisherwomen. The contribution of this study lies in strengthening family communication and gender studies within coastal communities by positioning communication as a key dimension for understanding power relations, women’s burdens, and their implications for child well-being.